Pruning the Banyan Tree?: Nature Conservation and State-Civil Society Relations in Singapore - Neo, Choon Tiong Harvey (Association of American Geographers, 2014)
100th Association of American Geographers Annual Meeting, Philadelphia, USA, 14-20 April 2004